Computer-aided design finite element modeling of different approaches to rehabilitate endodontically treated teeth - Da Fonseca, Gabriela Fernandes [UNESP]; De Andrade, Guilherme Schmitt [UNESP]; De Oliveira Dal Piva, Amanda Maria [UNESP]; Tribst, João Paulo Mendes [UNESP]; Borges, Alexandre Luiz Souto [UNESP] (Wolters Kluwer, 2018)
Background: Carious lesions and dental fractures cause weakening in the dental structure. In these situations, endodontic treatment and prosthetic rehabilitation using an intraradicular post are indicated. However, the postspace preparation of the root canal further weakens the dental remnant, especially if there is no ferrule present. This study aimed to evaluate the stress distribution in endodontically treated upper premolars treated with different rehabilitation approaches. Materials and Methods: An endodontically treated first upper premolar was modeled for finite element analysis. Three different approaches were carried out on this model: rehabilitation with fiberglass post (FCP), endocrown (ECW), or buildup. The models were exported in STEP format to the analysis software (ANSYS 17.2, ANSYS Inc., Houston, TX, USA). The solids were considered isotropic, homogeneous, and linearly elastic. A mechanical, structural static analysis was used as the criterion of maximum principal stress to show regions under tensile stress to evaluate the stress distribution in the restoration, cementation line, and root. A load of 400 N (90°) was applied to the lingual triangular ridge. The values of maximum principal stress in MPa were evaluated through colorimetric graphs. Results: Similar stress concentration was observed for all groups. However, the ECW group presented higher values in the restoration/cement interface and root dentin. Conclusions: All the treatment modalities had favorable mechanical behavior to support the masticatory loads; nevertheless, the ECW group presented a higher risk of detachment failure.
Keywords: Dental prosthesis; dental restoration; finite element analysis; permanent crowns; post and core technique